Age & Fairness in Economical Behaviour : An Experimental Investigation of Ultimatum Game - Tee, Jin Yee (2003)
Recently research on ultimatum bargaining, the fact that children often confront and use ultimatums and theories of developmental psychology all combine to suggest that studying children’s ultimatum behaviour will be particularly enlightening, both theoretically and with respect to the development of bargaining behaviour. The objectives of this paper are: 1) To provide further investigation of the development of bargaining behaviour in ultimatum games. 2) To show that age differences, especially between adolescents and adults, have an influence in the strategic behaviour and social preferences. 3) To identify whether of these adolescents and adults fairness taste were innate or learned through socialisation. The results from the experiments indicate that adolescents were fairer than the adults in the way they offer their share. In addition, adolescents accepted smaller offers as compare to the adults. Difference of age does affect the adolescents’ offer to other players and similarly, it does affect adolescents when responding to the offers. In dictator game, both adolescents and adults allocation of resource were indifferent. Also, the discussion focuses on the development of bargaining strategies and concerns for fairness.